Hygroscopic Properties of Nigerian Wood Brachystegla and Experimental Determination of Shrinkage Characteristics - Ezigbo, Veronica Obiageli; Obi, Juliana Chineze (European Journal of Scientific Exploration, 2019)
The current research is dedicated to the experimental determination of shrinkage characteristics ofBrachystegia nigeriawood on its linear, volumetric, and coefficient values with the hope of ascertaining its utilization potential as timber. Two study locations were randomly selected from defined vegetation zones of theguinea savannahfor the study. These are Anambra (guinea savanna)and Oyo (rain forest). Twenty tree samples of Brachystegia nigeriawere randomly selected and felled from which sixty wood specimens were extracted and prepared using Romanian standard for the research. The analysis of variance (ANOVA) was used to experiment demonstrated that the tree species has an average tangential linear shrinkage of 10.74%, radial linear shrinkage of 4.24%, longitudinal linear shrinkage of 1.10% and volumetric shrinkage of 18.10%. The coefficients of tangential, radial and longitudinal shrinkage were 0.00662, 0.00315 and 0.00060 respectively. The analysis of variance revealed insignificant differences of shrinkage between the two vegetation zones, the sampled trees as well as between the trunk sections.Since the shrinkage value of Brachystegianigeriawood compare favorably with some local wood species, used for timber,Brachystegic nigeriawood could be considered suitable for timber production.